Ryzyko upadłości przedsiębiorstwa - zastosowanie metod analizy czasu przeżycia - Mazurkiewicz, Mariusz; Wawrzynowski, Piotr (The Risk of Company's Bankruptcy - Usage of the Survival Models, 2007)
The article shows the use of Cox hazard model over the real data. The authors compared the efficiency of prediction of Cox model with the results from logit model and discrimination analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 163-173